AGRONOMIC AND ECONOMIC EFFICIENCY OF UREA TREATED WITH N-(n-butyl) thiophosphoric triamide APPLIED IN MAIZE CULTIVATION TOP-DRESSING (Nucleus, 2020)
Addition of NBPT (N-(n-butyl) thiophosphoric triamide) to the urea granule has been one of the alternatives to increase nitrogen fertilizer efficiency, but there are still doubts about the stability of its treatment after storage and influence on culture yield. The objective was to evaluate the agronomic and economic efficiency of urea treated with NBPT in maize culture due to different rates of N. The test was conducted in the experimental area of Mato Grosso do Sul Federal University, Campus of Chapadão do Sul, MS, using the experimental design of randomized blocks in factorial 4 x 3, consisting of four rates (0 , 60, 120, 180 Kg ha-1) and three sources of nitrogen (convencional urea, urea + Just treated with NBPT, urea + NBPT treated and stored for a year) with four repetitions. The use of Just treated urea with NBPT for top-dressing in maize culture presented more productive and economic efficiency than using conventional urea. The rate of 180 kg ha-1 of N applied in maize culture top-dressing has improved yield in 3,000 kg ha-1 and may be used by conventional urea treated with NBPT.